2018
DOI: 10.1111/bjhp.12296
|View full text |Cite
|
Sign up to set email alerts
|

Don't know responses to cognitive and affective risk perception measures: Exploring prevalence and socio‐demographic moderators

Abstract: Lower uncertainty for affective (vs. cognitive) absolute perceived risk items is consistent with research stating: (1) Risk perceptions are grounded in people's feelings about a hazard, and (2) feelings are easier for people to access than facts. Including affective perceived risk items in health behaviour surveys may reduce missing data and improve data quality. Statement of contribution What is already known on this subject? Many people report that they don't know their risk (i.e., risk uncertainty). Evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 48 publications
3
7
0
Order By: Relevance
“…People tend to conform their judgment with social or group normative standpoints in uncertain situations (Cialdini and Goldstein 2004), and may be less certain about cognitive than affective judgments (Janssen et al 2018). In line with this view, we observed that political orientation moderated the link between individual flooding experience and subjective attribution of flooding to climate change but not the link between individual flooding experience and climate change concern.…”
Section: Discussionsupporting
confidence: 76%
“…People tend to conform their judgment with social or group normative standpoints in uncertain situations (Cialdini and Goldstein 2004), and may be less certain about cognitive than affective judgments (Janssen et al 2018). In line with this view, we observed that political orientation moderated the link between individual flooding experience and subjective attribution of flooding to climate change but not the link between individual flooding experience and climate change concern.…”
Section: Discussionsupporting
confidence: 76%
“…40 This is consistent with the premise that, since affect and intuitions are more easily accessible than cognitions, 26,27,29,30 clarifying the intended item wording by conditioning the items may not be as important for feelings of risk items than for cognitive perceived likelihood items. That the effect of conditioning had similar effects on absolute and comparative items (hypotheses 3b and 4b) is also consistent with prior research 40 but remains unexplained. Future research should identify the mechanisms driving these effects and their implications for the development of health behavior theory and interventions.…”
Section: Discussionsupporting
confidence: 75%
“…However, we judge this unlikely, because other studies with fewer items also report that feelings items may be less vulnerable to DK responding. 40 Future studies should counterbalance the perceived risk items or randomly assign participants to receive conditioned or unconditioned perceived risk items.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is perhaps due to the lack of a clear theorization of the relationship and distinction between risk perceptions and uncertainty. Janssen et al (2018) considered uncertainty in terms of the “don’t know” responses to questions assessing risk perceptions. However, this implied an assumption that individuals do not experience uncertainty if they can indicate a risk judgment.…”
Section: Conceptualizing Uncertainty As a Metacognition Of Risk Percementioning
confidence: 99%